CALLUS INDUCTION, IN VITRO SHOOT REGENERATION AND HAIRY ROOT FORMATION BY THE ASSESSMENT OF VARIOUS PLANT GROWTH REGULATORS IN TOMATO (Solanum lycopersicum Mill.) - S. H. Shah; S. Ali; S. A. Jan; J. Din; G. M. Ali (Journal of Animal and Plant Sciences, 2015)
In vitro morphogenesis is greatly influenced by plant growth regulators (PGRs). The effect of different plant growth regulators was assessed on callus induction, in vitro shoot regeneration and hairy root formation in tomato. The maximum callus induction frequency was recorded culturing hypocotyls, while in vitro shoot regeneration frequency was significantly higher when leaf discs were used as explants. The highest callus induction frequency (67.48%) was recorded in cv. Rio Grande followed by Roma (62%) and Moneymaker (58.23%) on MS basal media along with 2.0 mg/l IAA and 2.5 mg/l BAP. Similarly, the highest in vitro shoot regeneration frequency (69.6 and 65.3%) was recorded in Rio Grande and Roma on MS media fortified with 0.1 mg/l IAA, 1.0 mg/l ZEA and 2.0 mg/l BAP, while in case of Moneymaker, the highest in vitro shoot regeneration frequency (67.3%) was obtained on MS media enriched with 0.1 mg/l IAA and 3.0 mg/l BAP. The highest hairy root formation frequency (100, 91.72 and 93.74%) was achieved in cvs. Rio Grande, Moneymaker and Roma, respectively on MS media supplemented with 0.1 mg/l IAA, 2.0 mg/l ZEA and 2.0 mg/l BAP. These optimized procedures would be applicable to other genotypes of tomato for the development of cultivars tolerant to abiotic stresses developed via Agrobacterium mediated transformation system.
Keywords: Hypocotyls; In vitro morphogenesis; Leaf discs; Plant growth regulators; Hairy roots